PARTICIPATORY MAPPING FOR DISASTERS IN TULUNGREJO VILLAGE, BUMIAJI SUB-DISTRICT, BATU CITY - Amiruddin, Lutfi; Rozalinna, Genta Mahardhika (University of Muhammadiyah Malang, 2020)
The ecological situation in Batu has a significant potential disaster, one of the areasthat have this is Tulungrejo village in the Bumiaji sub-district of Batu city. In general,there have been thirty-two disaster outbreaks in the Bumiaji sub-district; the areawith the most disaster risk is Tulungrejo village. Therefore, as an awareness ofemergency response situations, participatory mapping for disaster potential risk isessential to conduct by using the information of local people. This research appliedthe Participatory Geographic Information System (Pgis) as the mapping approach.The purpose of using this approach is to produce a disaster risk potential map asthe reference in determining the priority of disaster risk reduction based on theinformation that exists in the local area. This participatory mapping is an essentialpart of creating the social-technical resilience by the community.